Penggunaan Model Pembelajaran Make a Match Peningkatan Hasil Belajar Siswa pada Mata Pelajaran PKN Materi Keberagaman Budaya di Kelas IV MIS Amal Bhakti Perdamaian Kecamatan Binjai - Siti Hafsyah (Education & Learning, 2023)
One of the factors that can support success in a lesson is an effective and fun learning activity. To be able to create an effective and enjoyable learning atmosphere, teachers are expected to have models or methods as well as special media in learning. Various efforts that can be made by the teacher is to apply a learning model or method that is appropriate to the circumstances of the students. By maximizing the facilities available in the classroom and in the school environment. This Classroom Action Research aims to improve student learning outcomes in Civics subjects for Indonesian Ethnic Diversity through the use of the Make a Match learning model in Class IV MIS Amal Bhakti Perdamaan, Binjai District. This research was conducted at the beginning of the odd semester of the 2023-2024 academic year. These results indicate that there is an increase in student learning outcomes in the subject of Civics on the Diversity of Indonesian Tribes as evidenced by data that has increased from cycle I to cycle III. The average score of student learning outcomes in cycle I was 59.56 with a percentage of mastery learning of 47.06%, this value increased in cycle II with an average score of 67.94 with a percentage of 58.82%, increased again in cycle III with an average score of 78.97 with a percentage of 94%.